PESAN PERSUASIF VIDEO ANIMASI KAMPANYE SOSIAL "BERSATU UNTUK INDONESIA" (ANALISIS ISI VIDEO YOUTUBE GRAB) - Arina Safira Herland (2022)
Covid-19 has an impact on people's health, economy and social. Many Covid-19 prevention programs have started to be carried out, one of which is the Grab company which has created the "United For Indonesia" social campaign program. The social campaign in the form of an animated video on the Grab Indonesia Youtube account aims to persuade the public to participate in helping victims affected by Covid-19 by making donations. The purpose of this study was to determine whether the animated video for the social campaign "United for Indonesia" depicts a persuasive message based on the verbal and non-verbal elements contained in the video using a quantitative approach to content analysis methods. The research population consisted of verbal elements (23 lyrics, 9 texts) and non-verbal elements (24 illustrations, 21 movements, 21 backgrounds, 25 audio, 25 colors). Data were analyzed descriptively, presented in frequency and percentage. The coding was carried out by 2 people, to ensure objectivity using the inter-coder reliability with Scott's formula. The results obtained that the animated video "United for Indonesia" contains quite a lot of persuasive messages, namely verbal elements in the form of lyrics (96%), text (100%) and non-verbal elements in the form of illustrations (83%), movement (71%), background (52%), audio (44%), and color (76%). The results of the categorization of the content of persuasive messages between coders resulted in a large percentage weight for the invitation category for verbal elements and complementary categories for non-verbal elements. High reliability values are found in the text, lyrics, illustration, movement, and background analysis units, then low reliability values are found in audio and color. Key Word : Persuasive Message, Social Campaign, Animation Video